The impact of corruption on economic growth in SADC - Darlington Chizema; Ramos E. Mabugu; Christelle Meniago (Economies, 2025)
This study analyses the long-term impacts of corruption on economic growth within the Southern African Development Community (SADC) region, using data spanning 2005 to 2022. Through econometric modelling covering SADC countries, the research investigates the influence of corruption on the economic performance of the region. Employing descriptive statistics, panel unit root tests, and the autoregressive distributed lag pooled mean group model, the findings demonstrate that corruption, human capital, gross capital formation, trade openness, and government effectiveness significantly affect economic growth, whereas foreign direct investment does not. Corruption is believed to hinder economic progress by contributing to inefficient resource distribution, emphasising the need for robust anti-corruption strategies. Besides targeted anti-corruption measures, the research advises broader approaches such as enhancing institutional abilities, promoting transparency and accountability, and encouraging international cooperation. Advancing regional integration and leveraging technology to monitor and report corruption are also crucial. Moreover, promoting trade openness and human capital development can enhance economic growth. These comprehensive approaches aim to create a more transparent and efficient setting, ultimately boosting SADC's economic growth.
Keywords: 330; economic growth; corruption; development; ARDL; SADC